JOURNALISTIC CARICATURE TRAINING to FASILITATE YOUTH CREATIVITY - Erwin Kartinawati; Bening Tri Swasono (JURNAL PENGABDIAN TEKNOLOGI TEPAT GUNA, 2022)
This community service activity was carried out to provide training to students on journalistic caricatures. The training was intended for senior high school level students considering that their age was youth or adolescent. Teenagers usually had a lot of creative ideas that need to be explored and expressed positively. They had feelings and or opinions about the conditions that occur. All was to be appreciated better so their activity couldn't damage and pollute the surrounding environment, such as painting the walls of public facilities. Social media feeds also need to be posted with more exciting and brilliant uploads when giving specific reactions to social, political, or economic phenomena. With this journalistic caricature training and competition, students were also expected to know about (mass) media content production. In this way, students as members of society were passive public who consume media content and learn how mass media content was produced/presented to the public.